Analysis of the relationship between asthma and benign prostatic hyperplasia: A STROBE-compliant study. Issue 11 (19th March 2021) - Wee, Jee Hye; Bang, Woo Jin; Park, Min Woo; Byun, Soo-Hwan; Choi, Hyo Geun
Abstract : Abstract: The purpose of this study was to evaluate the association between asthma and benign prostatic hyperplasia (BPH) in an adult Korean population and to evaluate this association based on the treatment status of asthmatics. We utilized the Korean genome and epidemiology study health examinee 2004 to 2016 database. A total of 47, 186 participants (825 asthmatics and 46, 361 controls) were selected and their BPH histories were analyzed. We categorized the participants according to their asthma treatment status: "well controlled"; "being treated"; and "not being treated". The adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for BPH were analyzed using multiple logistic regression. Subgroup analyses were performed according to age (60 years). The results showed that the prevalence of BPH was higher among asthma patients (17.1%) than among controls (8.7%, P  < .001). Asthma patients had a higher risk of having BPH (OR = 1.64, 95% CI = 1.37–2.01, P  < .001) than controls, after adjustment for age, income, body mass index (BMI), smoking, alcohol consumption, frequency of physical activity, and the past medical diseases. The ORs for BPH were 1.35 (95% CI = 1.04–1.76) in those aged >60 years and 2.24 (95% CI = 1.70–2.96) in those aged ⩽60 years. The ORs for BPH were 1.82 (95% CI = 1.16–2.87, P  = .009) in the "well-controlled" group, 1.05 (95% CI = 0.74–1.49, P  = .794) in the "being treated" group, and 2.24 (95% CI = 1.69–2.97, P  < .001) in the "not being treated" group. We found that there is a correlation between asthma and BPH in the adult Korean population. There is a stronger association between asthma and BPH in younger adults and in those who are not receiving treatment for asthma.